The Reality Of Using The Moodle E-Learning Platform At The Algerian University Study On A Sample Of Professors From The Faculty Of Humanities And Social Sciences At The University Of Biskra - farzouli, mokhtar; seghiri, miloud; elkhamssa, ramdane (Journal of Social Sciences and Humanities, 2021)
This Study Aims To Highlight The Impact Of The Interaction Of Professors Researchers In The Promotion Of E-Learning In The Efforts To Develop And Improve University Education, And Considering That The Educational Process Is A Communication Process In All Its Components, This Study Is At The Heart Of The Specialty Of New Communication Technologies. The E-Learning Platform Moodle Is One Of The Newest And Most Widely Used E-Learning Platforms, And Although These Platforms Were Created To Promote E-Learning In The Academic Environment, Learning Process And Learning And Provided And Learning It Provided Many Avenues And Services For The Constituents, In This Study, We Tried To Answer The Main Question: What Is The Reality Of The Use Of The E-Learning Platform Moodel Among Professors Of The Faculty Of Humanities And Social Sciences Of The University Of Mohammed Khayder Biskra?